Cell-cell signaling controls Xylella fastidiosa interactions with both insects and plants - Newman, Karyn L. (National Academy of Sciences, 2004)
Xylella fastidiosa, which causes Pierce's disease of grapevine and other important plant diseases, is a xylem-limited bacterium that depends on insect vectors for transmission. Although many studies have addressed disease symptom development and transmission of the pathogen by vectors, little is known about the bacterial mechanisms driving these processes. Recently available X. fastidiosa genomic sequences and molecular tools have provided new routes for investigation. Here, we show that a diffusible signal molecule is required for biofilm formation in the vector and for vector transmission to plants. We constructed strains of X. fastidiosa mutated in the rpfF gene and determined that they are unable to produce the signal activity. In addition, rpfF mutants are more virulent than the wild type when mechanically inoculated into plants. This signal therefore directs interaction of X. fastidiosa with both its insect vector and plant host. Interestingly, rpfF mutants can still form in planta biofilms, which differ architecturally from biofilms in insects, suggesting that biofilm architecture, rather than a passive response to the environment, is actively determined by X. fastidiosa gene expression. This article reports a cell-cell signaling requirement for vector transmission. Identification of the genes regulated by rpfF should elucidate bacterial factors involved in transmission and biofilm formation in the insect.